State policy of ensuring demographic security: characteristics of basic concepts - Z.O. Hrytsyshena (Економіка, управління та адміністрування)
The article examines the theoretical and methodological aspects of the state policy of ensuring demographic security. The evolution of the concept of demographic security is analyzed. Scientific approaches to defining the concept of «demographic security» are systematized and generalized, among which the following are distinguished: security-protective, reproductive-dynamic and stabilization-development approaches. Based on a critical analysis of scientific sources, a comprehensive definition of demographic security has been formulated as a state of protection of the state, society and individual citizens from demographic threats, characterized by balanced quantitative and qualitative indicators population reproduction, optimal demographic structure and functioning of effective social institutions, which meets national interests and contributes to the sustainable development of the state at all levels. It is proposed to consider demographic security as an integrative system that includes three interrelated components: structural-quantitative, qualitative-reproductive and institutional-regulatory. A distinction is made between the concepts of «demographic policy» and «state policy for ensuring demographic security». It is determined that demographic policy is an integral part of the state policy of ensuring demographic security, focusing mainly on issues of fertility, mortality, marriage and migration, while the state policy of ensuring demographic security is a more complex concept that covers the entire set of demographic threats to national security. The author’s definition of the state policy of ensuring demographic security is proposed as a purposeful, systematic and cyclical activity of state authorities, implemented in interaction with civil society and business institutions, aimed at achieving optimal parameters of population reproduction, preserving its qualitative characteristics, regulating migration processes and preventing demographic threats through the development and implementation of relevant strategies, programs and measures, as well as monitoring their implementation. A cyclical model of state policy for ensuring demographic security is described, which reflects the relationship between the stages of policy formation and implementation, including problem definition, goal formulation, tool development, implementation, monitoring and evaluation of results. Attention is focused on the need for a comprehensive approach to ensuring demographic security, which takes into account the relationship between demographic processes and other areas of state policy, in particular economic, social, migration and territorial development policies.